The effect of roughness and top layer in solid particle impingement erosion of multilayer nanostructured nitride PVD coatings - Zahra Afshar; Meisam Nouri; Hassan Elmkhah; Naiming Lin; Yang Yang (Results in Surfaces and Interfaces, 2024)
The effect of the surface roughness of the coating and the composition of the upper layer on the solid particle erosion of multilayer nanostructured coatings applied via cathodic arc evaporation (CAEPVD) method was investigated. CrN/TiN nanostructured multilayer coating (TiN as the upper layer) and TiN/CrN nanostructured multilayer coating (CrN as the upper layer) were applied on 410 stainless steel through the CAEPVD method with the following architecture. 1) a bottom layer of Cr and CrN deposited on the substrate, 2) nanolayers of TiN and CrN deposited on the bottom layer alternately and 3) an upper layer of CrN or TiN deposited on the nanolayers. After applying the coating, half of the samples were polished to obtain smooth surfaces, while the other half remained unpolished, resulting in rough surfaces. Surface morphology, phases identification, adhesion, mechanical, and erosion behavior of the coatings were characterized using SEM, XRD, Rockwell adhesion measurements, nanoindentation test, and solid particle impingement, respectively. The nano-scale indentation results demonstrated that the hardness, Young's modulus, H/E, and H3/E2 of the CrN/TiN coating were 5.57, 1.42, 3.86, and 85.39 times larger than those of the substrate. For the TiN/CrN coating, the values were 4.04, 1.13, 3.53 and 51.68 times greater than those of the substrate. The results of the erosion test showed that the erosion mass loss for the CrN/TiN and TiN/CrN coatings decreased up to 73% and 67%, respectively. Additionally, surface smoothing improved erosion resistance by 40% for both coatings. This shows that the smoothed CrN/TiN nanostructured multilayer coating is an excellent candidate for increasing the erosion resistance due to the higher ratios of H/E and H3/E2 and smoother surface.